Exploring the cycle of violence: Own childhood experiences of violence and attitudes towards violence relate to female caregivers’ violent discipline - Faustine Bwire Masath; Tobias Hecker (Child Protection and Practice, 2025)
Background: Violence against children, including violent discipline, is widespread globally, particularly in low- and middle-income countries like Tanzania. However, evidence supporting the cycle of violence hypothesis in nations with a high prevalence of violent discipline is still scarce, especially concerning female caregivers. Objective: This study examined the association of female caregivers’ experiences of violent discipline in their childhood, as well as their approval of violent discipline, with their use of violent discipline against their children. Participants and setting: A total of 851 female caregivers (Mean (M) Age = 40.00 years, Standard Deviation (SD) Age = 11.392, Range: 17–91 years) of children (MAge = 12.58 years, SDAge = 1.43, Range: 8–18 years) participated in a cluster-randomised controlled trial aimed at preventing violent discipline by teachers in 12 schools across six regions of Tanzania. Methods: Binary logistic regression analyses were used to examine the association of female caregivers with and without experience of violent discipline in their childhood and those approving and not approving violent discipline with their use of physical and emotional violent discipline against their children. Results: More than 90 % of female caregivers reported having experienced violent discipline during their childhood. Also, about 95 % of female caregivers reported favourable attitudes towards violent discipline, 72.2 % had used one or more forms of physical violent discipline, and 84.8 % had used one or more forms of emotional violent discipline against their children in the past month. Female caregivers with a childhood experience of violent discipline and those with favourable attitudes towards violent discipline were significantly more likely to use both physical and emotional violent discipline (p < .05) against their child(ren). Conclusion: The findings highlight the need for designing and implementing effective interventions that challenge societal norms and practices endorsing violent discipline while promoting the education of female caregivers. This approach could decrease instances of violent discipline within families and help break the cycle of violence.